The Influence of Knowledge, Perception, and Attitude toward the Usage of Online Transportation Base Application among Housewives - Siti 'Ilmawati Sholihat; Mohamad Djem djem Djamaludin (Journal of Consumer Sciences, 2017)
This study aimed to analyze the influence of housewife’s knowledge, perception, attitude towards the use of online application based transportation. The sample of this study was 100 housewives, including 50 housewives from suburban area, and 50 housewives from urban areas. The results showed that average index score of knowledge and perception both in suburban and urban area had moderate category. Average index score of attitude of housewives in suburban area had a moderate category, and housewives in urban area had a good category. The duration of education, location, knowledge, perception and attitude have positive correlation with frequency of using online application based transportation. Results of regression analysis showed that age, location, knowledge, perception, and attitude positively influenced the frequency of using online application based transportation.